GERAKAN SALAFI DI LOMBOK (Harmoni, 2012)
The  school of Salafi  understands   Islam  teachings literary and limiting of intellectual role. Salafi canΓÇÖt accept other religious understanding beside theirs, as described by Sasak people. The Sasak  is an  indigenious ethnic  in Lombok. There are three culture mixed in that Island, Hinduism of Javanese old Kingdom, Islam  and Balinese Hinduism. Some of the  Sasak`s undertansding of theologic and ritual are parts of their culture or custome, such as human lifecycle, starting from birth, untill death. Salafi believes those traditions as bid`ah and opposite with Islam. The phenomena make tension in interaction among the peole and possibly become conflict.
Keywords: adat istiadat; bidΓÇÖah; salafi; sasak; tradisi; tradition